Cross Laminated Timber (CLT) Beams Loaded in Plane: Testing Stiffness and Shear Strength - Boggian, Francesco; Andreolli, Mauro; Tomasi, Roberto (Frontiers in Built Environment, 2019)
Cross Laminated Timber (CLT) is a relatively new timber product used in construction that has gained popularity over the last decade. The product itself is constituted by multiple glued layers of juxtaposed boards, usually arranged in an orthogonal direction between one layer and the adjacent ones. This particular structure brings several benefits, such as the possibility to use the same product both for walls and slabs, since it can bear in-plane and out-of-plane loads. However, the mechanical behavior differs from usual timber products, and research is still ongoing to achieve common agreement on standard procedures for testing products and theories for evaluating stresses for safety verifications. This paper focuses on the in-plane shear behavior of CLT and analyzes the existing methods to evaluate shear stresses. An experimental part then presents a four-point bending test of CLT beams with a specific geometry to induce shear failure. Results are reported both for the elastic range test, measuring the Modulus of Elasticity, and for the failure test to investigate shear behavior with regard to different mechanisms. Previously exposed methods are used for the calculation of shear stresses and to analyze the correspondence between them, and the results are then compared with other existing tests and values in literature. A new test setup for future research is eventually proposed.